PRELIMINARY ANTIMICROBIAL STUDY OF KANTAKARI (SOLANUM XANTHOCARPUM SCHRAD & WENDL) BY DITCH PLATE TECHNIQUE - Sayali, *Shintre; Ashok, Ramteke; Manju, Phadke; Vivek, Parab (International Journal of Ayurveda and Pharma Research, 2019)
Lower Urinary tract Infection (Lower UTI) is the second most common infection in human population. Escherichia coli is one of the microbial strain responsible for lower UTI in most of the cases. Standard antibiotics can control the infection but there is recurrence of episodes in many cases. Constant research is carried out in this field to discover new antimicrobial agents. It is difficult for the microorganisms to acquire resistance to herbs and the polycompounds in them. They may make potential and promising antimicrobial agents references from classical text of Ayurveda suggest Kantakari (Solanum xanthocarpum Schrad & Wendl) to be effective in urinary disorders. The antimicrobial activity of Kantakari was studied invitro in its traditional forms that is Swaras (juice), Kalka (paste) and Chuna (powder) against the strains of Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeuriginosa, and Candida albicans. The study was carried out by using ditch plate technique and zones of inhibition were measured and statistically analyzed. It was observed that juice form and paste were more effective than powder form. Escherichia coli strain was found to be sensitive to the juice, paste and powder samples of Kantakari. Klebsiella pneumoniae showed intermediate resistance as compared to other organisms. In conclusion of this study it was found that Kantakari has good antimicrobial potential and must be studied further.